Assessment of provisions on special investigative measures in the 2015 criminal procedure code and recommendation for complete - Nguyễn, Sơn Phước (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The special investigative measures is a completely new institution, first regulated in the 2015 Criminal Procedure Code. Therefore, it is inevitable that some shortcomings and limitations cannot be avoided, even though this is an important provision in the resolution of criminal cases. The article analyzes and evaluates some theoretical issues, the provisions of the 2015 Criminal Procedure Code on special investigative measures; regulations of some countries around the world revolve around this institution. On that basis, the author boldly made some proposals to complete the provisions of the 2015 Criminal Procedure Code on special investigative measures to improve the effectiveness of these measures in Vietnam in the future.